Pengaruh job stress, job insecurity dan Beban Kerja terhadap Turnover Intention karyawan Rumah Sakit Permata Keluarga Lippo Cikarang - Iskandar, Diki (DPPM Universitas Pelita Bangsa, 2023)
Service is an invisible product that provides satisfaction to customers, the spearhead of service is that employees are more comfortable and the more concerned employees are about their work, the better the results obtained by the company. This becomes a homework for company management on how to manage a system so that it is easily adapted by all parties to reduce the impact of turnover on employees. The purpose of this study is to analyze job stress, job insecurity and workload on turnover intention in employees of Permata Keluarga Hospital Lippo Cikarang. The research method used in this study is causal descriptive quantitative method. The sampling technique used was the slovin method with a population of 186 employees and a margin of error using 5%, resulting in a sample of 127 employees. The results and conclusions of this study show the influence on job stress and workload on turnover intention while job insecurity has a negative effect on turnover intention. Keywords: Job Stress, Job Insecurity, Workload, Turnover Intention